2014
DOI: 10.1051/matecconf/20141411006
|View full text |Cite
|
Sign up to set email alerts
|

Misorientation effect of grain boundary on the formation of discontinuous precipitation in second and third generation single crystal superalloys

Abstract: Abstract.[001] tilt artificial grain boundaries of Ni-based single crystal superalloys CMSX-4 and DD10 have been prepared by self-diffusion bonding. The microstructural stability of 0 ∼ 30 • artificial grain boundaries have been investigated after heat treatment at 1100 • C for 0 ∼ 300 h. TCP phases and cellular colony developed on boundaries are related to misorientation angle of the bonded boundaries of DD10 and DD10 alloys as well as the bonded boundaries of CMSX-4 and DD10 alloys. The heterogeneous nucleat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
2
1
Order By: Relevance
“…In the P phase, the amount of rhenium is about 20 at%. 30,38) , while in this study, the amount of Re was over 60 at%. Also, it was observed that the DP reaction is most likely to occur during aging which is controlled by grain boundary diffusion 39) , however, Re-rich particles have been detected in an as-cast sample without multiple steps of melting, casting and heat treatment 22) .…”
Section: Resultscontrasting
confidence: 44%
See 1 more Smart Citation
“…In the P phase, the amount of rhenium is about 20 at%. 30,38) , while in this study, the amount of Re was over 60 at%. Also, it was observed that the DP reaction is most likely to occur during aging which is controlled by grain boundary diffusion 39) , however, Re-rich particles have been detected in an as-cast sample without multiple steps of melting, casting and heat treatment 22) .…”
Section: Resultscontrasting
confidence: 44%
“…Misorientation of the grain boundary is an important factor in uencing on the precipitate formation and grain boundary migration because the grain boundary energy and migration rate are related to the misorientation angle of grain boundary 30) . Therefore, in high angle grain boundaries, the discontinuous precipitation (DP) reaction can easily occur in order to reduce the energy of the grain boundary.…”
Section: Resultsmentioning
confidence: 99%
“…Also, when compared to the composition of the TCP phases reported in the DP reaction, such as the P phase with an amount of rhenium of about 20 at. pct, [43,44] 6 , and R phase (Mo 31 Cr 18 Co 50 ), [1] the composition is also very different. In addition, TCP phases from the DP reaction form after a long aging time through grain boundary diffusion.…”
Section: Comparison Of the Formation Mechanism With A Conventionalmentioning
confidence: 99%